A metabolic database for biomedical studies of biopsy specimens by high‐resolution magic angle spinning nuclear MR: a qualitative and quantitative tool. Issue 1 (7th March 2019) - Ruhland, Elisa; Bund, Caroline; Outilaft, Hassiba; Piotto, Martial; Namer, Izzie‐Jacques
Abstract : Purpose: The aim of this study is to generate a metabolic database for biomedical studies of biopsy specimens by high‐resolution magic angle spinning (HRMAS) nuclear MR (NMR). Methods: Seventy‐six metabolites, classically found in human biopsy samples, were prepared in aqueous solution at a known concentration and analyzed by HRMAS NMR. The spectra were recorded under the same conditions as the ones used for the analysis of biopsy specimens routinely performed in our hospital. Results: For each metabolite, a complete set of NMR spectra (1D 1 H, 1D 1 H‐CPMG, 2D J‐Resolved, 2D TOCSY, and 2D 1 H‐ 13 C HSQC) was recorded at 500 MHz and 277 K. All spectra were manually assigned using the information contained in the different spectra and existing databases. Experiments to measure the T1 and the T2 of the different protons present in the 76 metabolites were also recorded. Conclusion: This new HRMAS metabolic database is a useful tool for all scientists working on human biopsy specimens, particularly in the field of oncology. It will make the identification of metabolites in biopsy specimens faster and more reliable. Additionally, the knowledge of the T1 and T2 values will allow to obtain a more accurate quantification of the metabolites present in biopsy specimens.